Examining the influence of parental support on academic procrastination: Self-concept as a mediator among Muslim university students - Eko, Dedek; Hasanuddin, Hasanuddin; Milfayetty, Sri (INSPIRA: Indonesian Journal of Psychological Research, 2024)
Procrastination is a common behavioral issue in the academic domain, characterized by the tendency to delay tasks. This study investigates the relationship between parental social support and academic procrastination, examining the mediating role of self-concept among students at Institut Syekh Abdul Halim Hasan Binjai. The population of the study comprised 612 students, with a sample of 242 respondents selected through random sampling. Data were collected using three scales: self-concept, parental support, and academic procrastination. Multiple regression analysis was employed to assess the relationships between variables. The findings reveal a significant negative relationship between parental support and academic procrastination. Additionally, a negative relationship is identified between parental support, mediated by self-concept, and academic procrastination. The study indicates that 24% of the variance in academic procrastination is accounted for by parental support through self-concept. The study concludes that higher levels of parental support enhance students' self-concept, which in turn significantly reduces academic procrastination. These findings underscore the importance of parental involvement in fostering positive academic behaviors among students.